Sistem Purchase Order terhadap Efisiensi dan Pengendalian Pengadaan Barang Operasional : Studi Kasus pada DoubleTree by Hilton Surabaya - Aldi Sinai Ferdianto Simbolon; Erna Sulistyowati (CV. ALIM'SPUBLISHING, 2026)
The Purchase Order (PO) system is an important component in the procurement of hotel operational goods because it functions as both an administrative document and an internal control tool that can maintain cost efficiency and minimize the risk of errors and fraud in purchase transactions. This study aims to analyze the implementation of the Purchase Order system implemented in the Finance Department of DoubleTree by Hilton Surabaya, evaluate its contribution to the efficiency and control of the procurement of operational goods, and identify the obstacles faced and the steps to solve them. The study used a descriptive method with a qualitative approach through participatory observation techniques and interviews with Purchasing, Cost Control, and Chef staff during a five-month internship period. The results of the study show that the PO system integrated with Supply Chain Management (SCM) is able to speed up the procurement administration process, support a balanced price comparison between price and quality, and strengthen control through a tiered approval mechanism by the Head of Department and Cost Control. However, obstacles are still found in the form of price or vendor input errors, approval delays, and sudden price changes from suppliers, which are overcome through document revisions, delegation of authority, and intensive coordination between parties. This research provides practical implications for hotel management in strengthening the accuracy of data input and emphasizing approval deadlines, as well as being a reference for further research on the application of technology-based PO systems in the hospitality industry.